An evaluation of the effectiveness of a computerized transcription system in a private general hospital - Bernardo, Catherine (Eulogio) 1970
Computerization is one of the major interventions adopted by healthcare organizations to improve their services. Several studies have proven that computer technology not only improved clinical services but also created a safer healthcare environment for patients through more efficient treatment procedures and reduced incidence of adverse drug events (ADE). For these reasons, a tertiary, general, private, 700-bed capacity hospital has adopted a computerized transcription system, the Harmony Computer System (HCS), to improve their drug administration procedure. This study aims to evaluate the effectiveness of this system in terms of reducing drug administration and time incidence of medication errors and in terms of user satisfaction with the new system. In evaluating the time saving benefit of the system, time and motion studies were conducted before and after computerization. Mean times for each process in the drug administration procedure namely: transcription, dispensing, transport and rug preparation and administration, pre-and post-computerization were compared using Student?s t test for independent groups with p≤0.05 considered as significant. Results showed that transport time significantly decreased from 51.85 to 20.71 minutes after computerization. Overall, the total drug administration time was reduced from 97.92 to 71.17 minutes (37.62%) after implementation of the computerized transcription system. Review of medication errors reports six (6() months before and six (6) months after computerization revealed that the number of reports on potential adverse drug events (ADE) during the transcription process increased from 0 to 20.2 events per 10,000 medication orders carried out. Actual ADEs on the other hand was reduced from 0.36 to 0.05 events per 10,000 medication orders. Potential ADEs during the dispensing process did not considerably change while actual ADEs increased from 0.03 to 0.18 events per 10,000 medication orders dispensed. Satisfaction survey using 5-point Likert scale was conducted among users of the system including nurses, pharmacists and clerks. Respondents were chosen using stratified random selection to ensure that all professions in all units were represented in the study. Eighteen (18) questions related to system characteristics, system benefits, software tools, orientation and training as well as overall satisfaction were included in the questionnaire. Areas for improvement were also rated according to importance and priority. Results showed that the users were satisfied with the new system with a mean overall satisfaction rating of 3.92 ± 0.68. Among the system characteristics, the respondents considered it easy to use (4.0 ± 0.74) and agreed that the system speeds up their work compared to paper ordering (4.21 ± 0.82) and improves their productivity (4.06 ± 0.61). From the list of areas with potential for improvement, system speed topped the survey with 58.1%, followed by information in drug menu with 56.9% and procedure simplification, 53.1%. Based on the results of the studies, the following recommendations may be considered to further improve the system: 1) create a separate module for pharmacy, 2) improve the drug database, 3) install additional features in the pharmacy module to enhance clinical functions, 4) implement computerized prescriber order entry (CPOE) system and 5) synchronize HCS with the accounting inventory system. Overall, this study shows that the computerized transcription system is effective in improving the hospital?s drug administration procedure by reducing drug administration time and by helping reduce incidence of adverse drug events during the transcription process. Also, the users showed positive overall satisfaction with the system.